2012
DOI: 10.1371/journal.pntd.0001872
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Visceral Leishmaniasis in Villages of Eastern Gedaref State, Sudan: An Exhaustive Cross-Sectional Survey

Abstract: BackgroundSince December 2009, Médecins Sans Frontières has diagnosed and treated patients with visceral leishmaniasis (VL) in Tabarak Allah Hospital, eastern Gedaref State, one of the main endemic foci of VL in Sudan. A survey was conducted to estimate the VL incidence in villages around Tabarak Allah.MethodsBetween the 5th of May and the 17th of June 2011, we conducted an exhaustive door-to-door survey in 45 villages of Al-Gureisha locality. Deaths were investigated by verbal autopsies. All individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 22 publications
(31 reference statements)
2
39
1
Order By: Relevance
“…The hazard of death among VL patients who had nasal bleeding was 2.6 times higher than those patients who didn’t have nasal bleeding. This result is consistent with the result of a study in Northern Ethiopia(Tigray), America and Sudan[5,10,21]. Nasal bleeding among VL patients occurs probably due to a combination of deficient clotting factor and platelet count, which increases the risk of death among VL patients[35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The hazard of death among VL patients who had nasal bleeding was 2.6 times higher than those patients who didn’t have nasal bleeding. This result is consistent with the result of a study in Northern Ethiopia(Tigray), America and Sudan[5,10,21]. Nasal bleeding among VL patients occurs probably due to a combination of deficient clotting factor and platelet count, which increases the risk of death among VL patients[35].…”
Section: Discussionsupporting
confidence: 90%
“…From Eastern Africa region, Sudan is the most affected country, followed by Ethiopia, Kenya, Somalia and Uganda[5]. According to a study in eastern Uganda, mortality rate among VL patients is 3.7% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between exposure and disease can be inferred from the age distributions of KA cases. KA due to L. infantum (also known as "infantile VL") typically affects children <10 years (Badaro et al, 1986a;Davies and Mazloumi Gavgani, 1999), whereas KA due to L. donovani tends to be in older children and young adults <30 years in some locations, or older in others (Hailu et al, 2009;Mueller et al, 2012;Burza et al, 2014;Hasker et al, 2013). The age distribution will depend upon the exposure history of the population and will likely vary over the course of an epidemic cycle which is thought to be about 10-15 years on the ISC (Dye and Wolpert, 1988).…”
Section: Natural History Of Vl Diseasementioning
confidence: 99%
“…We investigated for VL antibodies in serum specimens in our study cases using rK39 test, which showed prevalence rate 57.7% higher as compared with the prevalence rate from above mentioned studies [13].…”
Section: Discussionmentioning
confidence: 84%